Elevated MyoD1 levels expand genome-wide binding and the repertoire of regulated genes - Oscar N. Whitney; Gina M. Dailey; Joseph K. McKenna; Xavier Darzacq; Robert Tjian (Proceedings of the National Academy of Sciences, 2026)
Transcription factor (TF) upregulation accompanies many cellular state transitions, yet how increased TF abundance impacts gene regulation remains unclear. Two broad models are often invoked, whereby higher TF levels amplify the expression of preexisting target genes, or, by mass-action binding, expand genome engagement and regulation to lower-affinity sites. We sought to elucidate how these two regulatory modes contribute to cell differentiation in a well-characterized myogenic system by upregulating the expression of the myogenic TF MyoD1 in C2C12 myoblasts. Unexpectedly, elevated MyoD1 levels impaired myoblast fusion (a hallmark of myogenic differentiation), yet enabled robust contraction in myotubes that did form. Live-cell single-molecule imaging and CUT and RUN profiling revealed that elevated MyoD1 dosage increased total genome-wide chromatin binding and broadened genome occupancy by preferentially engaging lower-affinity sites. Integrating CUT and RUN with RNA sequencing (RNA-seq) experiments linked expanded MyoD1 binding to upregulation of cell adhesion genes. Cell mixing and fractionated RNA-seq experiments supported a two-population model in which an adhesion-gene-upregulated, unfused myoblast population supported contraction of myotubes formed by fusion-competent cells. Ectopic expression of several individual MyoD1-upregulated cell adhesion genes was sufficient to recapitulate the “off script” myotube contraction phenotype. Together, these results support a MyoD1 dose-dependent “spillover” model, in which increased TF abundance broadens cis-regulatory engagement and produces distinct cell differentiation outcomes.